2003
DOI: 10.1038/sj.onc.1206587
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction by several KIT juxtamembrane domain mutations

Abstract: Mutations of KIT receptor tyrosine kinase are found in the majority of patients with mastocytosis and in most gastrointestinal stromal tumors. Oncogenic KIT mutations in GISTs are located in the KIT juxtamembrane domain (JMD), while codon 816 in the KIT kinase domain is mutated in systemic mastocytosis. We describe and characterize a mutation in the KIT-JMD named KD27. We show that KD27 mutant is constitutively dimerized and phosphorylated. KD27 ectopic expression renders both the Ba/F3 cell line and primary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 49 publications
7
54
0
2
Order By: Relevance
“…[45][46][47][48][49][50] The importance of the JM domain in signaling is evident from several mutations, deletions and insertions in this domain that can lead to cancer. [51][52][53] In addition, recent studies have provided evidence for the active role of the JM domains in regulating RTK activity.…”
Section: Juxtamembrane Domainsmentioning
confidence: 99%
“…[45][46][47][48][49][50] The importance of the JM domain in signaling is evident from several mutations, deletions and insertions in this domain that can lead to cancer. [51][52][53] In addition, recent studies have provided evidence for the active role of the JM domains in regulating RTK activity.…”
Section: Juxtamembrane Domainsmentioning
confidence: 99%
“…As measured by 3 Hthymidine incorporation, D816V KIT-transformed Ba/F3 cells were resistant to treatment with imatinib ( Figure 3 19 Previous reports have shown that STAT3 is aberrantly phosphorylated by D816V KIT. 20,21 PCR of the KIT gene Using PCR of KIT exon 17 followed by direct sequencing or sequencing of cloned RT-PCR products, the D816V KIT mutation was detected in the patient's bone marrow at the time of initial presentation in April 2003 and from peripheral blood after completion of 1 cycle of PKC412. However, these methods could not detect the D816V KIT mutation in the bone marrow after 2 cycles of therapy or from peripheral blood obtained at the completion of 3 cycles of PKC412 (during disease progression).…”
Section: In Vitro Analysis Of the Effects Of Pkc412 On D816v Kit-tranmentioning
confidence: 99%
“…14,15 They include the classical phosphatidylinositol 3-kinase (PI3K) and extracellular signal-regulated kinase (ERK) pathways, as well as a number of signaling proteins activated by many cell-surface receptors such as p38, JNK, VAV, STAT-1, STAT-3, and STAT-5. Activation of PI3K is critical for both WT and mutant KIT in all models studied, while the activation of the mitogen-activated protein (MAP) kinases ERK-1 and ERK-2 appears to be dependent on the cellular context.…”
Section: Introductionmentioning
confidence: 99%